2010
DOI: 10.1055/s-0030-1258104
|View full text |Cite
|
Sign up to set email alerts
|

A New Effective Synthesis of Arene Mono- and Disulfonyl Chlorides

Abstract: Arene mono-and disulfonyl chlorides have been easily synthesized starting from the corresponding anilines via aqueous oxidative chlorination of S-aryl O-ethyl dithiocarbonates intermediates, aryl methyl sulfides, or from arenethiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Barbero et al reported a synthesis of (R)-1,1'-binaphthyl-2,2'-disulfonyl chloride ((R)-10) from commercially available (R)-1,1'-binaphthyl-2,2'-diamine ((R)-11) (Scheme 4). [14] This approach began by the diazotization of (R)-11, and the corresponding diazonium tetrafluoroborate (R)-12 was isolated. Compound (R)-12 was treated with KSCSOEt in acetonitrile to give the xanthate (R)-13.…”
Section: Synthesis Of Optically Pure Binsasmentioning
confidence: 99%
“…Barbero et al reported a synthesis of (R)-1,1'-binaphthyl-2,2'-disulfonyl chloride ((R)-10) from commercially available (R)-1,1'-binaphthyl-2,2'-diamine ((R)-11) (Scheme 4). [14] This approach began by the diazotization of (R)-11, and the corresponding diazonium tetrafluoroborate (R)-12 was isolated. Compound (R)-12 was treated with KSCSOEt in acetonitrile to give the xanthate (R)-13.…”
Section: Synthesis Of Optically Pure Binsasmentioning
confidence: 99%
“…The chemistry of these systems has seen fair less investigation than those based upon the 1,2-benzene scaffold. A number of reports have been published describing the synthesis of simple thioether compounds (D), [8][9][10][11] (E) [12,13] and (F) [14] (Figure 2). However, to date there has been no report of the acenaphthene derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The work conducted by Barbero, which describes the synthesis of E, was examining synthetic routes to arene mono-and disulfonyl chlorides which are key intermediates for the synthesis of strong Brønsted acids which are useful organocatalysts. [13] Longer chain alkyl groups have also been utilised including ethyl derivatives of naphthalene (G) [15] and biphenyl (H) [12] as well as a butyl analogue on naphthalene (I) [16] (Figure 2). Figure 3 (J-M) shows the phenyl analogues that have been prepared based upon these backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the corresponding cyclic aryl-sulfonimide, o-benzenesulfonimide, 25 worked similarly to dibenzenesulfonimide. As shown in Table 1, o-benzenesulfonimide was able to open the aryl-, alkyl-, and heteroaryl-oxazoline rings on substrates 1, 3, 8, 9, and 11, respectively, with yields ranging from 72% to 95%.…”
mentioning
confidence: 97%